2015
DOI: 10.1021/acscatal.5b00404
|View full text |Cite
|
Sign up to set email alerts
|

Organic-Free Synthesis of CHA-Type Zeolite Catalysts for the Methanol-to-Olefins Reaction

Abstract: Chabazite (CHA)-type zeolites are prepared from the hydrothermal conversion of faujasite (FAU)-type zeolites, dealuminated by high-temperature steam treatments (500−700°C), and evaluated as catalysts for the methanol-to-olefins (MTO) reaction. The effects of temperature and partial pressure of water vapor during steaming are investigated. Powder X-ray diffraction (XRD) and Ar physisorption data show that the steam treatments cause partial structural collapse of the zeolite with the extent of degradation increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 21 publications
3
65
0
Order By: Relevance
“…From fraction of tetrahedral Al (Al T /Al Total ) estimated from the 27 Al NMR and the bulk P/Al ratio, the ratio of phosphorous to tetrahedral Al (P/Al T ) is estimated to be 0.38 for CHA-S600-P. From our previous work [13], the ratio of acid sites measured by i-propylamine TPD to that measured by NH 3 TPD for CHA steamed at 600°C was 0.32. This ratio is equivalent to the ratio of accessible mesoporous and external surface acid sites M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 3 more Smart Citations
“…From fraction of tetrahedral Al (Al T /Al Total ) estimated from the 27 Al NMR and the bulk P/Al ratio, the ratio of phosphorous to tetrahedral Al (P/Al T ) is estimated to be 0.38 for CHA-S600-P. From our previous work [13], the ratio of acid sites measured by i-propylamine TPD to that measured by NH 3 TPD for CHA steamed at 600°C was 0.32. This ratio is equivalent to the ratio of accessible mesoporous and external surface acid sites M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The presence of mesopores after steam treatment of these materials, as indicated by Ar physisorption measurements, likely also contribute to the increased lifetimes of the steamed zeolites by allowing for greater accessibility of reactants to the acid sites in the remaining microporous regions. We have previously observed using NH 3 and i-propylamine TPD that steam treatment of high-aluminum CHA-type zeolites lead to decreased total Brønsted acid site densities while simultaneously increasing accessibility of the remaining acid sites via mesopores[13]. An optimal steaming temperature of 600°C for CHA was found that gave the best balance of intact acid sites and accessibility.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…SSZ-13 zeolites have been synthesized via various methods, including direct synthesis (from precursors of silica and alumina) and conversion of zeolite Y. For the synthesis of SSZ-13s, various templates, such as N,N,Ntrimethyl-1-adamantanamine iodide (TMAda-I) [5,7], TMAda-OH [8][9][10][11][12], choline chloride [13,14], copper-tetraethylenepentamine (Cu-TEPA) [15][16][17], tetraethylammonium hydroxide (TEA-OH) [18], benzyltrimethylammonium hydroxide [19], and N,N,Ndimethylethylcyclohexylammonium bromide [20] have been used despite several reports of its template-free [21][22][23][24] synthesis.…”
Section: Introductionmentioning
confidence: 99%